Unformatted text preview: + 1 , x ) = a G 1 ( y, x, a H ( y, x ) A 2 ) , G 2 ( y, x, a H ( y, x ) A 1 ) A . . . by deFnition H ( y + 1 , x ) = a G 1 ( y, x, H 2 ( y, x )) , G 2 ( y, x, H 1 ( y, x )) A . . . by hypothesis H ( y + 1 , x ) = a H 1 ( y + 1 , x ) , H 2 ( y + 1 , x ) A . . . deFnition of H 1 and H 2 . Now, H 1 ( y, x ) = a H ( y, x ) A 1 so H 1 is primitive recursive, and H 2 ( y, x ) = a H ( y, x ) A 2 so H 2 is primitive recursive. 1...
View
Full
Document
This note was uploaded on 07/14/2011 for the course COT 5310 taught by Professor Staff during the Spring '08 term at University of Central Florida.
 Spring '08
 Staff
 Recursion

Click to edit the document details